2010
DOI: 10.1038/nprot.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro angiogenesis: endothelial cell tube formation on gelled basement membrane extract

Abstract: A protocol is presented here for a rapid, quantitative and reliable in vitro angiogenesis assay that can be adapted for high throughput use. Endothelial cells are plated on a gelled basement matrix, their natural substrate, and form capillary-like structures with a lumen. The assay can be used to identify inhibitors or stimulators of angiogenesis, as well as genes and signaling pathways involved in angiogenesis. It has also been used to identify endothelial progenitor cells. This assay involves endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
516
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(527 citation statements)
references
References 28 publications
10
516
0
1
Order By: Relevance
“…Our analysis is also consistent with studies that identified a period in which the vascular plexus underwent a slight deformation after formation (14). On the other hand, the second observed phase of cell spreading (where the cells spread while exhibiting minimal movement, presumably forming filopodia and lamellipodia, before elongating to form cell-cell contacts) and the fourth observed phase of plexus stabilization (a distinct period where the plexus stabilizes before it rearranges) have not been identified as discrete events to our knowledge (14,15,34,35).…”
Section: Discussionsupporting
confidence: 72%
“…Our analysis is also consistent with studies that identified a period in which the vascular plexus underwent a slight deformation after formation (14). On the other hand, the second observed phase of cell spreading (where the cells spread while exhibiting minimal movement, presumably forming filopodia and lamellipodia, before elongating to form cell-cell contacts) and the fourth observed phase of plexus stabilization (a distinct period where the plexus stabilizes before it rearranges) have not been identified as discrete events to our knowledge (14,15,34,35).…”
Section: Discussionsupporting
confidence: 72%
“…We are aware that any in vitro assay is not more than an indication of what happens in vivo . In general, the tube formation assay is considered to be a quick and quantifiable way of measuring angiogenesis in vitro 48, 49. It is a useful method to determine growth factors that potentially play a role in vivo vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The cultured LN LECs readily formed tube structures at early P4 (n = 6 independent cell isolates) as well as late P22 passages (n = 2 independent cell isolates), with examples shown in Figure 3. Early and late LEC cultures therefore both maintain the same ability to migrate and form vessel-like structures.…”
Section: Jordan-williams and Ruddellmentioning
confidence: 99%